P022/O02 Distinct macrophage phenotype and bioenergetic profiles in rheumatoid arthritis. (March 2019) - Hanlon, MM; McGarry, T; Canavan, M; Low, C; Veale, DJ; Fearon, U
Abstract : Career situation of first and presenting author: Student for a master or a PhD. Introduction: Synovial macrophages play a key role in RA disease progression, however, the diversity and plasticity of macrophage subsets and their metabolic profile within the joint has yet to be elucidated. Objectives: To phenotype distinct macrophage subsets within the RA joint, and determine the metabolic and inflammatory function of RA macrophages compared to healthy controls (HC). Methods: Synovial-tissue biopsies from RA, PsA and OA, obtained through arthroscopy, were digested to yield a synovial single cell-suspension. Biopsy suspensions and synovial fluid mononuclear cells were analysed using advanced flow-cytometry with the following antibody panel (CD40, CD45, CD64, CD68, CD163, CD206, CD253). CD14+ monocytes were sorted from RA and HC bloods and differentiated/polarized into M1/M2 macrophages. Inflammatory (IL-8, -MCP-1, -IL1b, -CCR5, -IRAK1, -OSM) and metabolic (HIF1a, -PFKFB3, -PKM2, -LDHA, -HK2) markers were measured by RT-PCR, and phagocytosis by OVA luciferase-yellow assays. Glycolysis (ECAR) and oxidative phosphorylation (OCR) were quantified by Seahorse -XFE- technology. Results: RA synovial-tissue and fluid CD68+ macrophages displayed markers typical of both M1(CD40+CD253+) and M2(CD206+CD163+). A significant increase in frequency of CD68+ and CD64+ macrophages in synovial-tissue compared to fluid was observed (p<0.05), with significant increases in marker expression of CD40, CD163, CD206 (p<0.07). A spectrum of macrophage-subtypes within the inflamed joint was observed, with significant enrichment of a dominant double positive CD206+CD163+ macrophage subtype in the synovial-tissue versus synovial fluid demonstrated (p<0.05). Increased frequency of CD206+CD163+ macrophages and higher expression of activation marker CD40 were demonstrated in RA synovial-tissue compared to PsA and OA. M1 macrophages demonstrate a pro-glycolytic phenotype with significant increases in HIF1a, -HK2, -PKM2, -and PFKB3, compared to M2, effects exacerbated in RA macrophages compared to HC. In parallel, using seahorse-technology RA M1 and M2 macrophages displayed higher ECAR and OCR profiles, in addition to an increased ECAR:OCR ratio compared to HC (p<0.05), evidence that RA macrophages switch to a glycolytic profile. This was paralleled by increased intracellular-cytokines expression of IL-1b, -IL-6 and TNFa and genes expression of IL-8, -IL1b, OSM and MCP-1 (p<0.05). Finally, phagocytic ability of RA M1 was impaired compared to HC. Conclusions: We have identified, for the first time, a dominant macrophages subtype enriched in RA synovial-tissue. Furthermore, RA M1/M2 have distinct metabolic profiles associated with differences in key inflammatory mediator and phagocytosis function. Disclosure of Interest: None declared.